Giant string Elschnig’s pearls (Ukrainian Journal of Ophthalmology, 2025)
Background. Elschnig pearls are cells that migrate from the   capsule of the lens and can cause posterior subcapsular opacity (PCO) Case: 29 years old male PO extracapsular cataract extraction two years ago, came for decreased visual acuity secondary to PCO. After the first capsulotomy 8 months ago, he developed giant Elschnig pearls at the edge of the capsulotomy forming a pearl necklace that cause the poor vision again.Conclusion. More studies are needed on the evolution of the disease to help assess the best time to give invasive treatment or wait for spontaneous disappearance of the pearls.
Keywords: pearls of Elschnig; opacity; capsulotomy